Netnography Study of Warganet's Response to Flexing Action on ASN in @official iNews Youtube Video "Mario Dandy Satriyo, Official's Son Likes to Show Off Wealth on Social Media #iNewsSiang 23/02" - ni wayan suryatini (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2024)
The surge in social media usage has sparked a trend known as the flexing phenomenon, where individuals, not just celebrities but also regular people, showcase their wealth. This shift was highlighted by a viral YouTube video on the Official iNews channel titled " Mario Dandy Satriyo Anak Pejabat Gemar Pamer Harta di Media Sosial #iNewsSiang 23/02" drawing criticism from viewers. This research employs the netnography method to analyze netizens' reactions to the video. It reveals three main themes in the comments: a cynical perspective on flexing, calls for appropriate consequences for those who flaunt their wealth, and skepticism towards governmental institutions. The predominant sentiments expressed are anger and disappointment, with negative responses prompting demands for government transparency regarding the potential link between flexing and corruption allegations.